Diabetes mellitus como factor de riesgo de cáncer de páncreas. Hospital Instituto Ecuatoriano de Seguridad Social. Riobamba. 2018- 2020 - Johanna Andrea, Paucar Moromenacho (2021)
ABSTRACT Diabetes Mellitus occurs in a high percentage of patients diagnosed with pancreatic cancer; therefore, it was established that there is a positive and significant relationship in which diabetes mellitus has a risk factor for the development of pancreatic cancer. At the Hospital General IESS Riobamba in the Surgery service in the outpatient, hospitalization, and emergency área, sixty-two patients diagnosed with pancreatic cancer were analyzed, of which 66% have a history of diabetes. The average age of the participants was 62 years in the group of people with diabetes; of these, the female gender represented 55.7% and the male 44.3%. 100% of the patients are from the Sierra region. 59% with a history of smoking consumption and 34% alcohol consumption. The main sign of admission of the patients was abdominal pain with 29%, followed by jaundice and abdominal mass with 24% of patients with a history of diabetes. 80% of patients with a history of diabetes had a family history of pancreatic cancer. In the group of diabetics, 49% had pancreatitis. The tumor marker Ca19-9 in the diabetes group was positive in76% of the cases. The most frequent group was endocrine type tumor with histopathologyof adenocarcinoma in 59%. Regarding the stage of cancer, in diabetic patients, 23.3% were diagnosed, and stage IV was the one that was found the most with 56%. At the same time, the survival rate was 34%. Keywords: Diabetes mellitus, pancreatic cancer, glucose, hyperglycemia, adenocarcinoma, mortality. Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258